2003
DOI: 10.1099/mic.0.25927-0
|View full text |Cite
|
Sign up to set email alerts
|

n-Hexane sensitivity of Escherichia coli due to low expression of imp/ostA encoding an 87 kDa minor protein associated with the outer membrane

Abstract: Most Escherichia coli strains are resistant to n-hexane. E. coli OST4251 is a n-hexane-sensitive strain that was constructed by transferring the n-hexane-sensitive phenotype from a n-hexane-sensitive strain by P1 transduction. OST4251 is resistant to diphenyl ether, which is less harmful than n-hexane to micro-organisms. The genetic determinant responsible for this subtle difference in the solvent resistance is mapped at 1·2 min on the E. coli chromosome. Nucleotide sequence analysis showed that IS2 and IS5 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…Amongst several of the proteins identified in rhizobia grown in treatment media were proteins regulated by sigma factor ơ E , which typically regulates genes required to combat stress in the periplasmic space of E. coli (Abe et al, 2003;Aono et al, 1994;Dartigalongue et al, 2001). The identification of these stress proteins corroborates the findings of the membrane integrity study that peat extract challenges cells of rhizobia during growth.…”
Section: General Discussion and Conclusionsupporting
confidence: 73%
See 1 more Smart Citation
“…Amongst several of the proteins identified in rhizobia grown in treatment media were proteins regulated by sigma factor ơ E , which typically regulates genes required to combat stress in the periplasmic space of E. coli (Abe et al, 2003;Aono et al, 1994;Dartigalongue et al, 2001). The identification of these stress proteins corroborates the findings of the membrane integrity study that peat extract challenges cells of rhizobia during growth.…”
Section: General Discussion and Conclusionsupporting
confidence: 73%
“…This protein, often referred to as Imp/OstA (increased membrane potential/organic solvent tolerance), is a minor outer membrane protein and is the product of the imp,ostA gene region (Abe et al, 2003;Aono et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…We identified LptD as a protein whose correct folding was affected by the absence of DsbC. The synthetic phenotype of the surAdsbC mutant fits well with the identification of LptD as a DsbC substrate, because strains expressing low levels or mutated versions of LptD also are sensitive to antibiotics (28,31). Regarding the growth defect exhibited by the surAdsbC mutant at low temperatures, we propose that it results from perturbations in the lipid content of the OM caused by problems in the LPS insertion process.…”
Section: Discussionmentioning
confidence: 54%
“…Considering all these, we concluded that the n-hexane-sensitivity of OST4251 was caused by the lower production of the OstA protein. 4) Meanwhile, from the comprehensive analysis of E regulon by Dartingalongue et al, a E -dependent transcription of ostA was identified at À227 nucleotides far upstream from the initiation codon of ostA. 5) In this paper, we demonstrated identification of two new promoters responsible for the constitutive expression of ostA.…”
Section: Transcriptional Analysis Of the Osta/imp Gene Involved In Ormentioning
confidence: 98%
“…Instead, we found that IS2 was integrated at À83 bp from the initiation codon of ostA in OST4251. 4) The integration of IS2 at this position seemed to disrupt the putative promoter sequence. Western blotting analysis showed that amount of OstA protein in OST4251 was significantly decreased compared with that in JA300, supporting this idea.…”
Section: Transcriptional Analysis Of the Osta/imp Gene Involved In Ormentioning
confidence: 99%